Failure analysis of the mobile elevating work platform. (April 2015) - Bošnjak, Srđan M.; Gnjatović, Nebojša B.; Momčilović, Dejan B.; Milenović, Ivan L.J.; Gašić, Vlada M.
Highlights: Failure of the extending structure is investigated. Experimental–numerical investigations were conducted. Both 'operating-in' and 'manufacturing-in' defects caused the discussed failure. Abstract: This paper presents an investigation of the accident which occurred during startup of the extending structure from the transport position. In order to clarify the causes of crack occurrence along almost the entire surface of the lever cross-section, the authors performed visual, experimental (chemical composition, tensile properties, microhardness) as well as metallographic examinations. Stress states in the critical zone are defined by applying the finite element method (FEM). Based on the investigation results it was concluded that the lever breakdown is predominantly caused by both the 'operating-in' defect (the malfunction of the limit switch) and the 'manufacturing-in' defect (poor weld quality). The investigation results presented in this paper are important because same or similar problems could arise in supporting structures of various types of transportation, construction and mining machines.